Systemic MCP-1 Levels Derive Mainly From Injured Liver and Are Associated With Complications in Cirrhosis - Queck, Alexander; Bode, Hannah; Uschner, Frank E.; Brol, Maximilian J.; Graf, Christiana; Schulz, Martin; Jansen, Christian; Praktiknjo, Michael; Schierwagen, Robert; Klein, Sabine; Trautwein, Christian; Wasmuth, Hermann E.; et al. (Frontiers in Immunology, 2020)
Background & Aims: Monocyte chemotactic protein 1 (MCP-1) is a potent chemoattractant for monocytes. It is involved in pathogenesis of several inflammatory diseases. Hepatic MCP-1 is a readout of macrophage activation. While inflammation is a major driver of liver disease progression, origin and role of circulating MCP-1 as a biomarker remains unclear. Methods: Hepatic CcL2 expression and F4/80 staining for Kupffer cells were measured and correlated in a mouse model of chronic liver disease (inhalative CCl4 for 7 weeks). Next, hepatic RNA levels of CcL2 were measured in explanted livers of 39 patients after transplantation and correlated with severity of disease. Changes in MCP-1 were further evaluated in a rat model of experimental cirrhosis and acute on chronic liver failure (ACLF). Finally, we analyzed portal and hepatic vein levels of MCP-1 in patients receiving transjugular intrahepatic portosystemic shunt insertion for complications of portal hypertension. Results: In this mouse model of fibrotic hepatitis, hepatic expression of Ccl2 (P=0.009) and the amount of F4/80 positive cells in the liver (P<0.001) significantly increased after induction of hepatitis by CCl4compared to control animals. Moreover, strong correlation of hepatic Ccl2 expression and F4/80 positive cells were seen (P=0.023). Also, in human liver explants, hepatic transcription levels of Ccl2 correlated with the MELD score of the patients, and thus disease severity (P=0.007). Experimental model of ACLF in rats revealed significantly higher levels of MCP-1 plasma levels in ACLF (P= 0.028) and furthermore correlation of hepatic Ccl2 expression (R=0.69, P=0.003). Particularly, plasma MCP-1 levels did not correlate with peripheral blood monocyte Ccl2 expression. Finally, higher levels of MCP-1 were seen in the hepatic compared to the portal vein (P=0.01) in patients receiving TIPS. Similarly, positive correlation of MCP-1 with Child-Pugh score was observed (P=0.018). Also, in the presence of ACLF, portal and hepatic vein levels of MCP-1 were significantly higher compared to patients without ACLF (both P=0.039). Conclusion: Circulating levels of MCP-1 mainly derive from the injured liver and are associated with severity of liver disease. Therefore, liver macrophages contribute significantly to disease progression. Circulating MCP-1 may reflect the extent of hepatic macrophage activation.